2021
DOI: 10.1021/acs.jafc.1c03788
|View full text |Cite
|
Sign up to set email alerts
|

Using Fecal DNA Metabarcoding to Investigate Foraging Reveals the Effects of Specific Herbage on the Improved n-3 Fatty Acid (PUFA) Composition in the Longissimus Dorsi Muscle of Grazing Tan Sheep

Abstract: Understanding the natural diet of grazing sheep can help fulfill their nutritional requirements and positively affect the quality of their meat. Emerging fecal DNA (fDNA) metabarcoding technology can provide more accurate estimates for the dietary composition of free-ranging animals. This study has shown that pasture feeding can promote deposition of n-3 polyunsaturated fatty acids (PUFAs) in Tan lambs' muscle and decrease the ratio of n-6/n-3 fatty acids (FAs), and thus, we investigated the dietary compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…For PUFAs, the balance of n-3 PUFAs (including EPA and DHA) and n-6 PUFAs is an important index used to evaluate the nutritional value of meat quality for humans [ 45 ]. Previous studies of our team have found that grazing model increased the content of n-3 PUFAs and n-6 PUFAs and reduced the ratio of n-6/n-3 in LD muscle, which is more beneficial to human health [ 6 ]. The substantial positive association between EPA and DHA in rumen and EPA and n-3 PUFAs content in muscle indicated that the rumen of grazing lambs produced more EPA and DHA and thus potentially up-regulated the n-3 PUFAs content in muscle, contributing to better lamb meat quality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For PUFAs, the balance of n-3 PUFAs (including EPA and DHA) and n-6 PUFAs is an important index used to evaluate the nutritional value of meat quality for humans [ 45 ]. Previous studies of our team have found that grazing model increased the content of n-3 PUFAs and n-6 PUFAs and reduced the ratio of n-6/n-3 in LD muscle, which is more beneficial to human health [ 6 ]. The substantial positive association between EPA and DHA in rumen and EPA and n-3 PUFAs content in muscle indicated that the rumen of grazing lambs produced more EPA and DHA and thus potentially up-regulated the n-3 PUFAs content in muscle, contributing to better lamb meat quality.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that meat quality is strongly related to fatty acid composition, especially the proportion of PUFAs. Our previous results found that while indoor feeding increased daily gain, it enhanced the proportion of n-6/n-3 PUFAs, which negatively affected meat quality [ 6 ]. Similarly, it has been reported that the transcription of FADS2 could affect the endogenous transformation of long-chain PUFAs, reducing the bioavailability of n-3 PUFAs and promoting the accumulation of n-6 PUFAs [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations